Another New Year, Will the Chinese Residents Wear Face Masks Again? A Cross-Sectional Survey - Shen, Xin; Yan, Shijiao; Cao, Hui; Feng, Jing; Lei, Zihui; Zhao, Yuxin; Nui, Zhenyu; Han, Xiaotong; Lv, Chuanzhu; Gan, Yong (Frontiers in Public Health, 2021)
Background: As more and more countries enter the low-transmission phase, maintaining prevention awareness among the population is critical to preventing a secondary outbreak. With large-scale interpersonal communication, whether Chinese residents can maintain a high awareness of prevention and control and adhere to the use of masks during the Chinese New Year of 2021, which is worth studying. Methods: A cross-sectional survey was conducted in China from 4 to 26 February 2021. Convenient sampling strategy was adopted to recruit participators. Participants were asked to filled out the questions that assessed questionnaire on face masks using. Descriptive statistics were used to assess the public's mask-wearing behaviors. A binary logistic regression analysis was performed to identify the risk factors affecting the mask-wearing behaviors. Results: A total of 2,361 residents filled out the questionnaire. In the mixed-effect logistic regression analysis, Chinese residents who were older (OR=7.899, 95%CI=4.183-14.916), employed (OR=1.887, 95%CI=1.373-2.594), had a chronic disease (OR=1.777, 95%CI=1.307-2.418), reused face masks (OR=22.155, 95%CI=15.331-32.016) and have read the face mask instructions (OR=3.552, 95%CI=1.989-6.341) were more likely to use face masks in interpersonal communication during the Spring Festival; while people who were caused breathing discomfort by face masks (OR=0.556, 95%CI=0.312-0.991) and considered that using masks repeatedly is wasteful (OR=0.657, 95%CI=0.482-0.895) were not more likely to use. Conclusions: Our results revealed that, 83.86% of people wore face mask during the Chinese New Year; however, there remain some aspects that require further promotion. By investigating the use of masks and influencing factors by Chinese residents during the Spring Festival, we can reflect the prevention awareness of the residents during the low transmission period of the COVID-19, which can provide a reference for Chinese and global public health policy makers.